Interkulʹturiaâ variativnostʹ naučnogo teksta: k postanovke problemy - Černâvskaâ, Valeriâ E. (Stylistyka, 2021)
In her article Valeria E. Chernyavskaya sets the following questions: Can the cognitive styles have national specificity? Ifthe answer is positive, to what extent do they influence the selection of standardized, regularly repeating in the typical communicative conditions lexical units and text structures by passing scientific knowledge? How markedly does the cultural specificity reveal itself in the processes of utterance formation in scientific communication? The cultural specificity of a text is treated by the author as a prototypical feature of texture, characterized by high or low validity. The texts reflecting the intellectual (spiritual) life of the society would normally be culturally universal and contain minimum of specific national features intruding into their text-formation model. To this type the author ascribes, on the one hand, such text kinds as prayer, parable, parody, and, on the other hand, scientific texts, monographs, articles. The scientific text irrespective of the language it has been written in reflects the universals of the text-formation model, which makes it the vehicle of scientific knowledge in its ontological, gnoseological, methodological sense and contributes to the scientific thought continuity and progress. In the process of text formation in its contents and language aspects the selection of specific language elements and forms depends greatly on the author's social and cultural purposes. This visualizes itself in the discrete forma! differences between the text "formation moduses" in German, English, Russian, etc. languages. Stili, scientific texts are naturally most unmarked in terms of cultural specificity against the texts reflecting the materiał, industrial and everyday activities, such as sale advertisements, competitive applications, references, characters, notices on failure to pay debt, condolences, etc. These texts are characterized by linguistic prominence of the specific, non-universal national and cultural markers.